Customer Loyalty As A Mediating Variable In The Relationship Between Purchasing Decisions, Digital Marketing, And Brand Image Among Generation Z (A Study On Skintific Cosmetic Products) - Setiawan, Ainur Rahim; Syakur, Abd.; Fatimah, Siti; Isaac Mahkmut, Khalilah Daud (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This study aims to analyze the influence of digital marketing, brand image, and consumer loyalty on purchase decisions of Skintific products among Generation Z female consumers in East Java. The research model employs Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to test the relationships between variables. The results show that digital marketing significantly influences consumer loyalty, which in turn affects purchase decisions. Brand image also positively impacts consumer loyalty, although its direct influence on purchase decisions is weaker than that of consumer loyalty. Furthermore, consumer loyalty acts as a mediator that strengthens the influence of both digital marketing and brand image on purchase decisions. This finding emphasizes the importance of effective digital marketing and a positive brand image in enhancing consumer loyalty, which ultimately drives sustainable purchase decisions. This study provides insights for companies in developing more targeted marketing strategies, especially in strengthening the emotional connection between brands and consumers through digital marketing.